GENDER STEREOTYPES IN ENGLISH LANGUAGE TEXTBOOKS USED IN UZBEKISTAN: A CRITICAL DISCOURSE ANALYSIS - Zokirova Marjona Xislatjon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Annotation: This paper critically examines gender stereotypes present in English language textbooks used in Uzbekistan through the lens of Critical Discourse Analysis (CDA). It explores how language and imagery in textbooks reinforce traditional gender roles and contribute to shaping learners’ perceptions of gender. The study analyzes textbook content to identify biased representations and discusses the implications for language education and gender equality. Recommendations for developing more inclusive and balanced educational materials are provided.